Your turn : a CEO's guide to leading a business turnaround - Bergmans, Bas (Routledge, 2026)
A groundbreaking exploration into the intricate art of business turnarounds and swift recovery - qualified by a career's worth of insights - in Your Turn the message is startlingly clear: a turnaround is a one-chance-only experience. This is 'do or die,' and if you understand that in time and act accordingly by following a robust, comprehensive, data-driven approach to survival, your company stands a good chance of weathering the storm.Your Turn is a practical guide for executives to lead their own business turnarounds. With meticulous detail and respected leadership insights, the author has built a step-by-step approach that has served him well in delivering successful business turnarounds.Packed with real-world business examples and instructive models, Your Turn is an indispensable resource for CEOs, board members and senior leadership looking to drag their company out of a distressed situation and back into a thriving enterprise.